Neuro-Fuzzy based Controller for a Three- Phase Four-Wire Shunt Active Power Filter - Mridul Jha; S.P. Dubey (International Journal of Power Electronics and Drive Systems (IJPEDS), 2011)
This paper describes the application of a novel neuro-fuzzy based control strategy which is used in order to improve the Active Power Filter (APF) dynamics to minimize the harmonics for wide range of variations of load current under various conditions. To improve dynamic behavior of a three phase four-wire shunt active power filter and its robustness under range of load variations, adaptive hysteresis band with instantaneous p-q theory is used with the inclusion of neural network filter for reference current generation and fuzzy logic controller for DC voltage control. The proposed control scheme for “split-capacitor” converter topology is simple and also capable of maintaining the compensated line currents balanced, irrespective of unbalancing in the source voltages & deviation in the capacitor voltages. The results presented in MATLAB-SIMULINK software in this paper clearly reflect the effectiveness of the proposed APF to meet the IEEE-519 standard recommendations on harmonic levels.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.93